Disabled people, poverty and health public policies: Nursing care in the community appearance. - William Cesar Alves Machado; Amanda de Souza Santos (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2007)
Case study extracted of institutional research for the quality life and health promotion of the disabled people resident in a low income community in Juiz de Fora, Minas Gerais state, Brazil, carried out in the term of 2006-2006. Scenery which focuses a couple with deficiency living a poverty situation, unemployment and chronic disease, in which purpose was identify the difficulties faced by the disabled people, in a poverty situation who live in needed comunities for a regular access to the insured services of health public policies for the segment. The question which places is: Which are the difficulties pointed by disabled people who live in a low income community related to the access to the health public policies? It is concluded that we should invest to became satisfactory the execution of our political-social role related with the attendace of people care needs and families of few resources in the communities, especially to those neighbors to university campuses, giving example to the future professionals and waking up them to the aware amplification, especially, sharing information about rights to access the available of health public policies.